PENGUATAN MEREK DAN KEMASAN PADA PRODUK UMKM DESA JAMBEARUM KECAMATAN PATEBON KABUPATEN KENDAL - Ahmad Dwi Nurdiyanto; Endro Pramono; Riyono Riyono; Hesti Ristanto; Sukirman Sukirman (LPPM Universitas Bina Bangsa, 2024)
Brands and packaging in the business world have a big influence on the electability of a product, where they are a distinguishing mark in trading activities, especially goods or services of the same type, and provide quality assurance therein. As in the activities carried out by the ITB Semarang Community Service Team, the aim and target is generally to increase the value of traded products by collaborating with MSMEs in Jambearum Village, Patebon District, Kendal Regency. The benefits and advantages expected in this activity are that MSME products can have a higher selling value before and after using the brand and packaging, so that they can increase business opportunities and economically grow the standard of living of the community, especially in Jambearum Village, Patebon District, Kendal Regency. It is hoped that the results of this activity will provide knowledge about brands and apply it to MSME products